Маркетингові дослідження споживацьких переваг на регіональному ринку - Соколова, Л. В.; Верясова, Г. М. (The Academy of Management and Administration in Opole, 2013)
The selection of the product’s assortment that best matches the needs of consumers and determines required volume of sales for the enterprise’s planning. Consumer market segmentation procedure based on company’s assortment portfolio was realized. Factors that shape consumer preferences to product in various segment groups were identify and consumer preferences for specific market segments are determined.
Keywords: споживацькі переваги; маркетингові дослідження; споживацька поведінка; автомобільний ринок України; сегментація ринку; експертна оцінка; marketing researchers; consumer behavior; car; market segmentation; consumer preferences